2011
DOI: 10.1103/physrevlett.107.010603
|View full text |Cite
|
Sign up to set email alerts
|

Generic Transient Memory Formation in Disordered Systems with Noise

Abstract: Out-of-equilibrium disordered systems may form memories of external driving in a remarkable fashion. The system "remembers" multiple values from a series of training inputs yet "forgets" nearly all of them at long times despite the inputs being continually repeated. Here, learning and forgetting are inseparable aspects of a single process. The memory loss may be prevented by the addition of noise. We identify a class of systems with this behavior, giving as an example a model of non-brownian suspensions under … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
149
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(167 citation statements)
references
References 19 publications
15
149
3
Order By: Relevance
“…These systems all support the intuition that (i) the more times an input is presented the stronger the memory becomes, and (ii) random noise is detrimental to memory retention. However, both attributes are violated by multiple transient memories, which have been seen in traveling charge-density waves [5,6] and predicted for sheared non-Brownian suspensions [7,8]. The experiments reported here on sheared suspensions demonstrate that noise can stabilize this form of memory retention.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…These systems all support the intuition that (i) the more times an input is presented the stronger the memory becomes, and (ii) random noise is detrimental to memory retention. However, both attributes are violated by multiple transient memories, which have been seen in traveling charge-density waves [5,6] and predicted for sheared non-Brownian suspensions [7,8]. The experiments reported here on sheared suspensions demonstrate that noise can stabilize this form of memory retention.…”
mentioning
confidence: 56%
“…Keim and Nagel [7] described how multiple transient memories could occur in a simplified model of a suspension under cyclic shear: When sheared repeatedly between strain amplitudes γ = 0 and γ = γ 1 , a suspension can organize into a reversible steady state, thereby encoding a memory of γ 1 . The memory appears as a sudden drop in reversibility as the strain amplitude is swept past γ 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present system, with thousands of degrees of freedom, highly nonlinear and hysteretic equations of motion is a paradigm for chaotic behavior; therefore, it is surprising it exhibits a disordered absorbing state. The absorbing state dynamics found in nonBrownian suspensions at low Reynolds number are capable of encoding a rudimentary memory of the system's driving history (23), yet in these systems noise is required to retain memories beyond a single shear amplitude. Recent simulations found that dense amorphous solids can retain multiple memories in a similar fashion, but without the need for added noise (24).…”
Section: Discussionmentioning
confidence: 99%
“…As the strain amplitude γ t increases beyond some value γ * t , particles can no longer avoid each other and the system undergoes a dynamical "absorbing state" transition from the absorbing phase to a phase in which the system continually visits new configurations. Models [3,[5][6][7][8] have linked this transition to variants of directed percolation [8][9][10], which represents a broad class of non-equilibrium phase transitions [1].…”
mentioning
confidence: 99%